2017
DOI: 10.1111/ene.13275
|View full text |Cite
|
Sign up to set email alerts
|

Non‐obstructive carotid atherosclerosis and patent foramen ovale in young adults with cryptogenic stroke

Abstract: This study demonstrates that NOCA is common in young adults with CS. NOCA is negatively associated with PFO. Detecting NOCA is an important component of stroke investigation in young adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 22 publications
1
14
0
Order By: Relevance
“…18,23 This hypothesis is supported by several studies that highlighted the significance of non-stenotic carotid plaques as a cause of ischemic stroke. 36--43…”
Section: Discussionmentioning
confidence: 99%
“…18,23 This hypothesis is supported by several studies that highlighted the significance of non-stenotic carotid plaques as a cause of ischemic stroke. 36--43…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the AF‐ESUS (Prediction of Atrial Fibrillation after Embolic Stroke of Undetermined Source) study showed that new incident AF is less frequently detected in patients with ESUS and carotid plaques compared to those without [18]. Similarly, in young adults with cryptogenic stroke, carotid plaques were associated with the absence of PFO [41]. Both latter studies show that carotid plaques act as a competing stroke aetiology to other established stroke aetiologies, and hence, support their role as an underlying cause of ESUS.…”
Section: Discussionmentioning
confidence: 99%
“…In a study of 68 patients with embolic stroke, including 45 ESUS, the presence of high-risk plaque features on carotid ultrasound (ulceration, thickness ≥ 3 mm, and echolucency) was independently associated with detection of atrial fibrillation on admission or during follow-up (OR = 4.5, 95% CI: 1.0–19.6) ( 41 ). Fourth, in some patients with ESUS diagnosed using the current clinical definition, non-stenotic carotid plaques often coexist with other potential causes of stroke, including atrial fibrillation (8.5%) ( 15 ), intracranial atherosclerosis (8.4%) ( 42 ), PFO (5–9%) ( 43 , 44 ), and atrial cardiopathy (2.4%) ( 45 ).…”
Section: Challenges Of Establishing Causal Link With Strokementioning
confidence: 99%